El acoso escolar y su relación con los trastornos de bulimia y anorexia en los estudiantes de 13 a 18 años de la Unidad Educativa Pio Jaramillo Alvarado, Loja. Periodo 2019 - Loaiza Briceño, Carlos Fabián (2020)
In the past few years the incidence of bullying has increased in educational institutions, being the predecessor and maintainer of physical, academic, social and psychological issues, the literature shows that ,who receives it and, who practices it and everyone involved in bullying may present psychological disorders more frequently compared to those who do not have this type of exposure, mainly in the case of those who receive it, they seem to have more difficulties in managing emotional distress, and from that they can establish a pathological relationship with eating, presenting eating disorders during adolescence, the most prevalent being bulimia and anorexia, the same ones that cause a lot of emotional, physical, social, and cognitive distress, which can be difficult to manage in severe cases. The objective of the present study was to determine the relationship between bullying and bulimia and anorexia disorders. A descriptive-correlational and cross-sectional design was carried out, in which 172 students from the Unidad Educativa Pio Jaramillo Alvarado participated, aged between 13 and 18 years old, who were selected through non-probabilistic sampling tests. The instruments used were the Cisneros School Harassment Test, the Edinburgh BITE Bulimia Test and the EAT-40 Food Attitudes Test. The results suggest that there is a positive correlation between bullying and the presence of bulimia and anorexia nervosa, which indicates that when the level of bullying increases, the presence of bulimia and anorexia nervosa increases. Key Words: bullying, adolescents, bulimia nervosa, anorexia nervosa